Removal of ammonia in water systems using cell immobilization technique in surrounding environment. (2021) - Varna Vishakar, V.; Hari Haran, N.; Vidya, C.; Ashik Mohamed, M.
Abstract: Cell immobilization can be characterized as any strategy that restrains the free development of cell. The Sequencing Batch Reactor is utilized for the expulsion of alkali utilizing Nitrifying Bacteria by immobilized in sodium alginate beads. The ammoniacal nitrogen removal efficiency was evaluated at different pH from 7 to 9 and different nitrogen loading rates from 150 to 350 mg/L and hydraulic retention times (HRT) of 24, 48 and 72 h. The optimization of operating parameters such as pH, nitrogen loading rate and HRT was studied. The influent and effluent was analyzed for ammoniacal nitrogen, nitrite nitrogen and nitrate nitrogen. The highest removal of ammoniacal nitrogen was accomplished (89%) at pH 8 and the nitrogen loading rate of 350 mg/L with 72 h hydraulic retention time. The result indicates that the removal efficiency of ammoniacal nitrogen increase with increase in HRT and Nitrogen loading rate. Smelling salts oxidizing microorganisms were immobilized by polyvinyl liquor (PVA) and sodium alginate. The immobilization conditions and smelling salts oxidation capacity of the immobilized microscopic organisms were explored. The accompanying immobilization conditions were seen to be ideal: PVA-12%; sodium alginate-1.1%; calcium chloride-1.0%; inoculum focus-1.3 immobilized balls/mL of immobilized medium; pH-10; and temperature-30 °C. The immobilized smelling salts oxidizing microscopic organisms displayed solid alkali oxidation capacity significantly subsequent to being reused multiple times. The smelling salts nitrogen expulsion pace of the immobilized alkali oxidizing microscopic organisms arrived at 90.30% under the ideal immobilization conditions. When contrasted and smelling salts oxidizing microorganisms immobilized by sodium alginate alone, the microscopic organisms immobilized by PVA and sodium alginate were better with deference than pH opposition, the quantity of reuses, material cost, heat obstruction, and alkali oxidation capacity.